2020
DOI: 10.1007/jhep01(2020)194
|View full text |Cite
|
Sign up to set email alerts
|

Finite family groups for fermionic and leptoquark mixing patterns

Abstract: We employ a bottom-up and model-independent technique to search for non-Abelian discrete flavour symmetries capable of predicting viable CKM and PMNS matrices alongside of special patterns of leptoquark couplings. In particular, we analyze patterns derived when an ultra-violet flavour theory is assumed to break to global Abelian symmetries in Standard Model fermion masses and new Yukawa-like terms sourced by the leptoquark representation. The phenomenology of different classes of these 'simplified models' can … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 130 publications
(304 reference statements)
1
38
0
Order By: Relevance
“…RFS therefore provide a powerful, bottom-up means of understanding observed patterns of flavour mixing in a rather modelindependent way, as the only assumption made thus far is that the accidental flavour symmetries of the SM mass sector encoded in (4) are in fact the global RFS of a complete flavour theory broken as in (1) or its analogues. 2 In this way the RFS formalism defines a set of 'simplified flavour models,' which can easily be extended to BSM constructions as well -see [35] for a recent application of RFS to the Yukawa sector of multi-Higgs doublet models, where they were shown to be capable of controlling dangerous flavour-changing neutral currents alongside of fermionic mixing, and [31,32] where it is demonstrated that they can also structure the flavour patterns of leptoquark couplings (we also address some of these models in Sect. 4 below).…”
Section: The Infrared Lagrangianmentioning
confidence: 99%
See 4 more Smart Citations
“…RFS therefore provide a powerful, bottom-up means of understanding observed patterns of flavour mixing in a rather modelindependent way, as the only assumption made thus far is that the accidental flavour symmetries of the SM mass sector encoded in (4) are in fact the global RFS of a complete flavour theory broken as in (1) or its analogues. 2 In this way the RFS formalism defines a set of 'simplified flavour models,' which can easily be extended to BSM constructions as well -see [35] for a recent application of RFS to the Yukawa sector of multi-Higgs doublet models, where they were shown to be capable of controlling dangerous flavour-changing neutral currents alongside of fermionic mixing, and [31,32] where it is demonstrated that they can also structure the flavour patterns of leptoquark couplings (we also address some of these models in Sect. 4 below).…”
Section: The Infrared Lagrangianmentioning
confidence: 99%
“…In what follows we will use the bottom-up approach to 'reconstructing' NADS first discussed in [20,23], but recently applied to a class of BSM leptoquark models in [31,32]. Here one assumes that the RFS generators form the complete generating set for G F ,L,Q , such that the latter are recovered upon using GAP to close all elements of the former:…”
Section: Closing Ultraviolet Flavour Groupsmentioning
confidence: 99%
See 3 more Smart Citations